Strategi ASN Kementerian Agama dalam Mendorong Wakaf Uang Produktif di Kalimantan Tengah - Noorhasanah (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes that cash waqf is one of the strategic Islamic philanthropic instruments in supporting social and economic development. However, its implementation among civil servants (ASN) in the Ministry of Religious Affairs of Central Kalimantan Province still faces various obstacles. The ideal condition expecting active participation from ASN in the cash waqf movement has not been realized due to low waqf literacy, lack of integration with digital systems, and the absence of technical policies at the regional level. This study aims to analyze policy strategies that can promote the structured and sustainable implementation of cash waqf among ASN. A qualitative approach with a case study design was used. Data were collected through document studies, focused interviews, and literature review. The analysis applied the theoretical frameworks of Public Participation (Cohen & Uphoff), Change Agent (Rogers), and Substantive Rationality (Weber) to explore the roles of actors, the change process, and the socio-religious motivations of ASN. The findings indicate that the absence of integrated waqf literacy in ASN development, the lack of internal change figures, and weak institutionalization are the main challenges. The conclusion of this study emphasizes the need for affirmative policy at the regional level. The main recommendation is the issuance of a Circular Letter by the Head of the Regional Office of the Ministry of Religious Affairs of Central Kalimantan that mandates the integration of cash waqf literacy into the ASN development system, in order to foster productive, structured, and sustainable participation.